The engineering design primer - Richards, Keith L. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"Created to support senior-level courses/modules in product design, K. L. Richard's ENGINEERING DESIGN PRIMER reflects the author's deep experience in engineering product management and design. The combination of specific engineering design processes within the boader context of creative, team-based product design, makes this the ideal resource for project-based coursework. Starting with design concepts and tasks, the text then explores materials selection, optimisation, reliability, statistics, testing, and economic factors- all supported with real-life examples. Student readers will gain a practical perspective of the work they'll be doing as their engineering careers begin"--
OCLC-licensed vendor bibliographic record.
Keywords: Product design; Engineering design; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Design / General